2022
DOI: 10.1038/s41467-022-30913-4
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of cytotoxic tissue-resident CD8+ T cells and CCR6+CD161+ CD4+ T cells in the nasal mucosa following mRNA COVID-19 vaccination

Abstract: Vaccines against SARS-CoV-2 have shown high efficacy in clinical trials, yet a full immunologic characterization of these vaccines, particularly within the human upper respiratory tract, is less well known. Here, we enumerate and phenotype T cells in nasal mucosa and blood using flow cytometry before and after vaccination with the Pfizer-BioNTech COVID-19 vaccine (n = 21). Tissue-resident memory (Trm) CD8+ T cells expressing CD69+CD103+ increase in number ~12 days following the first and second doses, by 0.31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 46 publications
5
41
1
Order By: Relevance
“…In contrast, identical assays were unable to detect any T cells specific for Spike or any other SARS-CoV-2 proteins in the upper airway of almost all vaccinated only individuals despite the presence of Spike-specific T cells in their peripheral blood. Even though we cannot exclude that some vaccine-induced Spike-specific T cells might be present in the upper airway immediately after vaccination boost or be present in our samples at frequencies lower than the detection limit of our assay (ELISpot assay were performed with ∼5–10 × 10 3 T cells), our results do not confirm the extremely high frequency of Spike-specific CD8 + T cells recently reported in the nasal cavity 2 and 6 mo after vaccination ( Ssemaganda et al, 2022 ). Instead, our results are in line with the inability to detect a robust Spike-specific T cell response in the BAL of naive vaccine recipients ( Tang et al, 2022 ).…”
Section: Resultscontrasting
confidence: 88%
See 1 more Smart Citation
“…In contrast, identical assays were unable to detect any T cells specific for Spike or any other SARS-CoV-2 proteins in the upper airway of almost all vaccinated only individuals despite the presence of Spike-specific T cells in their peripheral blood. Even though we cannot exclude that some vaccine-induced Spike-specific T cells might be present in the upper airway immediately after vaccination boost or be present in our samples at frequencies lower than the detection limit of our assay (ELISpot assay were performed with ∼5–10 × 10 3 T cells), our results do not confirm the extremely high frequency of Spike-specific CD8 + T cells recently reported in the nasal cavity 2 and 6 mo after vaccination ( Ssemaganda et al, 2022 ). Instead, our results are in line with the inability to detect a robust Spike-specific T cell response in the BAL of naive vaccine recipients ( Tang et al, 2022 ).…”
Section: Resultscontrasting
confidence: 88%
“…Finally, while a recent study reported the presence of a very high frequency of Spike-specific T cells (≤10–20% of total nasal T cells) in the airway of mRNA vaccinated individuals ( Ssemaganda et al, 2022 ), others detected Spike-specific T cells only in BAL of SARS-CoV-2–infected convalescents and not in BAL of vaccinated-only individuals ( Tang et al, 2022 ). Thus, SARS-CoV-2–specific tissue-resident T cells were detected in the upper and lower airway of infected or healthy individuals, but the impact of parenteral vaccination or infection on the breadth and magnitude of SARS-CoV-2–specific T cells needs clarifications.…”
Section: Introductionmentioning
confidence: 97%
“…As the SARS-COV-2 entry-and infection-pathway primarily involves the respiratory tract with mucosal tissue, the mucosal immunity mediated by tissue-resident T cells and IgA antibodies becomes of particular interest. Notably, expansion of nasal tissue-resident CD69 + CD103 + CD8 + T cells were detected after mRNA vaccination [21] and, as others and we have shown [12], SARS-CoV-2-specific IgA antibodies increased in plasma after vaccination. These data indicate a development of tissue-localized humoral and cellular mucosal immunity after intramuscular COVID-19 vaccination.…”
Section: Discussionsupporting
confidence: 81%
“…A goal of vaccination is to induce the type of immune response that most closely approximates natural immune protection against infection, while eliminating risks of disease. For COVID-19, despite some controversy 56 , human vaccinees to parenteral SARS-CoV-2 do not appear to induce robust airway-resident antigen-specific T cells, unlike those who experienced natural infections 57,58 . This highlights the potential of next-generation COVID-19 vaccines to improve mucosal and systemic immune responses through modulation of T cells.…”
Section: Discussionmentioning
confidence: 99%